Bibliometric structure of IJCHM in its 30 years. Issue 12 (9th December 2019) - Mulet-Forteza, Carles; Genovart-Balaguer, Juanabel; Merigó, José Maria; Mauleon-Mendez, Emilio
Abstract : Purpose: The International Journal of Contemporary Hospitality Management is a leading international journal in the field of hospitality and tourism management. It was started in 1989, and it turns 30 years old this year. To celebrate this anniversary, this paper presents a bibliometric overview of the publication and citation structure of the journal over the past 30 years. The purpose of this paper is to identify the relevant issues in terms of keywords and topics and who is achieving better results in terms of authors, universities and countries. Design/methodology/approach: The Scopus database is used to collect the bibliographical material. A graphical mapping of the bibliographic data is developed by using VOSviewer software. It produces graphical maps with several bibliometric techniques, including co-citation, bibliographic coupling and co-occurrence of keywords. Findings: The results indicate that English-speaking countries are producing the highest number of articles in the journal, followed by Asian institutions, with the Hong Kong Polytechnic University as the most productive institution. Originality/value: To the best of the authors' knowledge, there are no papers that present a general overview of the publication and citation structure of this journal. Its 30th anniversary is a good moment to develop this study.